Rise of the Colorado Plateau: A Synthesis of Paleoelevation Constraints From the Region and a Path Forward Using Temperature-Based Elevation Proxies - Heitmann, Emma O.; Hyland, Ethan G.; Schoettle-Greene, Philip; Brigham, Cassandra A. P.; Huntington, Katharine W. (Frontiers in Earth Science, 2021)
The Colorado Plateau’s complex landscape has motivated over a century of debate around various aspects of its formation history. Key to this debate is understanding the timing and processes of surface uplift of the greater Colorado Plateau region, and its interactions with erosion, drainage reorganization, and landscape evolution. While the number of proposed constraints on the region’s surface uplift history has grown with the introduction of new paleoelevation proxies, there remains controversy over the robustness of paleoelevation estimates and associated uncertainties. Here, we synthesize existing paleoelevation estimates from the region and evaluate them in light of recent proxy advancements and in the paleo-topographic context inferred from geologic, stratigraphic, and geomorphic records. Paleoelevation data support hypothesized multi-stage uplift since the Laramide and imply that buoyancy may have been attained by the mid-Miocene. However, our analysis of proxy methods highlights the need for reevaluation of deposits and exploration of understudied deposits to fill knowledge gaps. We argue that there are opportunities to leverage advancements in temperature-based paleoaltimetry to refine the surface uplift history, for instance via systematic comparison of the clumped isotope and paleobotanical thermometry methods to lacustrine carbonates that span the region in both space and time.